Error Analysis in Translating Bahasa Indonesia into English - Berutu, Hotma; Dewi, Utami; Daulay, Sholihatul Hamidah; AR, Mhd. Faisal Abadi; Izar, Julisah; Nasution, Muhammad Muslim (Universitas Tidar, 2024)
Interlanguage is a transitional stage in language learning, where a person’s language ability moves from their first language (mother tongue) toward the other language. It is important to note that interlanguage is distinct from the mother tongue and the second/foreign language. This study examines the translation errors made by students when translating from Bahasa Indonesia to English during their interlanguage stage. The study aims to investigate (1) how students translate at this stage, (2) the types of errors they make, and (3) the most frequent errors. Using descriptive qualitative and content analysis methods, ten seventh-grade junior high school students participated in this study whose mother tongue is Bahasa Indonesia, and English is a foreign language/target language. For the instrument, this study uses an individual sentence translation test. The students were instructed to translate four unrelated sentences each, with a time limit of one minute per sentence. The researcher uses sources of error theory from Richard and Lott. The findings indicate that (1) most students tend to transfer the rules of their mother tongue into English. (2) Out of 40 sentences, it found 18 contained errors, leading to 26 mistakes: 8 interference errors (7.7% transfer of structure, 23% interlingual), and 18 intralingual errors (11.5% incomplete application of rules, 30.8% false concept hypothesized, and 27% overgeneralization). Meanwhile, (3) the most frequent error is false concept hypothesized, followed by overgeneralization, interlingual errors, incomplete application of rules, and transfer of structure errors.